Genetic variation in the PPARA gene is associated with simvastatin-mediated cholesterol reduction in the Rotterdam Study. (August 2013) - de Keyser, Catherine E; Becker, Matthijs L; Uitterlinden, André G; Hofman, Albert; Lous, Jan J; Elens, Laure; Visser, Loes E; van Schaik, Ron HN; Stricker, Bruno H
Aim: Recently, minor alleles of two strongly linked polymorphisms in the PPARA gene, rs4253728 G>A and rs4823613 A>G, were related to decreased CYP3A4 expression and activity. We studied whether they were associated with the cholesterol-lowering effect of simvastatin.Materials & methods: We identified 123 incident users with cholesterol measurements before and after starting statin therapy in a prospective population-based cohort study. Associations between PPARA polymorphisms and change in total and low-density lipoprotein (LDL)-cholesterol levels were analyzed using linear regression.Results: The minor G allele of the rs4823613 A>G polymorphism was associated with a 0.258 mmol/l (95% CI: -0.470 to -0.046) and a 0.294 mmol/l (95% CI: -0.495 to -0.093) larger reduction in total and LDL-cholesterol, respectively, after starting simvastatin therapy. Results were similar for the rs4253728 G>A polymorphism.Conclusion: The minor alleles of the PPARA rs4253728 and rs4823613 polymorphisms are associated with a better total and LDL-cholesterol-lowering response to simvastatin, possibly through influence on CYP3A4. Original submitted 13 February 2013; Revision submitted 8 May 2013